Graphene nano composite material and preparation method thereof
Through the synergistic effect of APTES functionalization, polyvinyl alcohol grafting and nanoTiO2, the problem of graphene prone to agglomeration in polyurethane matrix is solved, the mechanical properties and dispersion of the material are improved, and high-performance graphene nanocomposite materials are formed.
Patent Information
- Application Number
- CN202411518580.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Graphene is prone to agglomeration in a polyurethane matrix, resulting in a degradation of performance, and the strong van der Waals force between its sheets affects the dispersion and interface interaction of the material.
The introduction of aminosilane groups through APTES functionalization treatment, combining the synergistic effects of polyvinyl alcohol grafting and nanoTiO2, enhances the dispersion and interface binding of graphene in the polyurethane matrix, prevents the agglomeration of the sheet, and passes in situ polymerization and intersecting The use of coupling agents forms a highly crosslinked polyurethane network.
The mechanical properties, toughness and thermal stability of graphene nanocomposites are significantly improved, the interfacial bonding strength is enhanced, the brittleness caused by agglomeration is avoided, and the material is impact-resistant and photocatalytic properties are imparted.
Smart Images

Figure CN119306914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a graphene nanocomposite material and a preparation method thereof. Background Art
[0002] Since graphene was first successfully exfoliated in 2004, this material, which consists of carbon atoms connected by sp 2 Two-dimensional single-layer materials formed by close hybrid arrangement have quickly become the forefront of nanomaterial research due to their excellent physical, chemical and mechanical properties. Graphene not only has an extremely high specific surface area, excellent electrical and thermal conductivity, but also exhibits excellent mechanical strength and flexibility. However, pure graphene still faces some limitations in practical applications, such as difficult processing, easy agglomeration and limited functionalization. Therefore, compounding graphene with other materials to prepare graphene-based nanocomposites has become an important strategy to improve its comprehensive performance and broaden its application areas. Although graphene has many excellent properties, during the preparation process, single-layer graphene usually inevitably introduces certain defects. These defects may affect the performance of graphene to a certain extent. However, the appropriate introduction of defects has a positive effect on the preparation and performance improvement of graphene-based nanocomposites, and can effectively improve the interfacial interaction between graphene and the matrix material, thereby enhancing the comprehensive performance of the material.
[0003] Polyurea is a type of polymer material formed by the reaction of isocyanate and amine. It is widely used in protective coatings and high-performance elastomeric materials due to its excellent wear resistance, chemical corrosion resistance and high elasticity. Compared with polyurethane, polyurea system does not contain ester bonds, so it is less sensitive to moisture and exhibits better water resistance and chemical resistance. Polyurethane is a polymer material formed by the reaction of isocyanate and polyol. It has a variety of physical forms and good mechanical properties, wear resistance and flexibility. It is widely used in building materials, automotive parts, foam plastics and coatings. Introducing graphene into polyurea or polyurethane matrix can significantly enhance the mechanical strength of the composite material and improve its electrical conductivity and thermal conductivity. In addition, the lamellar structure of graphene has an excellent shielding effect, which significantly improves the composite material in terms of UV resistance, fire resistance and gas barrier properties. For example, graphene can effectively block the penetration of oxygen and water vapor, thereby greatly improving the weather resistance and anti-aging properties of the material. In the development of polyurea or polyurethane-based graphene nanocomposites, the strong van der Waals forces between graphene sheets easily lead to sheet agglomeration, which in turn affects the performance of the material. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a graphene nanocomposite material and a preparation method thereof.
[0005] The technical effect of the present invention is achieved by the following technical scheme: a method for preparing a graphene nanocomposite material, wherein the graphene nanocomposite material comprises graphite powder, APTES, polyvinyl alcohol, nano-TiO2, polyethylene glycol, trimethylolpropane and isocyanate; Preferably, the specific preparation steps of the graphene nanocomposite material are as follows: S1: Preparation of graphene oxide; Preparation of graphene oxide using a modified Hummers method; S2: introduction of aminosilane groups into graphene oxide; S3: Grafting polyvinyl alcohol and nano-titanium dioxide; through the action of initiator ammonium persulfate, polyvinyl alcohol is grafted onto the graphene oxide introduced with aminosilane groups in step S2, and then the surface-modified nano-TiO2 is introduced; S4: In-situ polymerization grafting modified graphene oxide and polyurethane polyol to obtain a graphene nanocomposite material; by selecting a hydrophilic polyol polyethylene glycol diol, adding a dibutyltin dilaurate catalyst and a trimethylolpropane crosslinking agent, a graphene nanocomposite material is prepared.
[0006] Preferably, in step S1, the specific preparation steps of the graphene oxide are as follows: A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature to 0-5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add potassium permanganate, raise the temperature to 35-40°C after the addition is complete, stir and react for 12-24 hours, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution for 3 times, dry at 60°C to constant weight, and obtain graphene oxide; Preferably, in step A1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:24mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:5-6mL:1g; Preferably, in step S2, the introduction of the aminosilane group is specifically prepared as follows: B1: The graphene oxide prepared in step A1 is dispersed in anhydrous ethanol, and ultrasonically treated at 200W for 30-60min to obtain a graphene oxide dispersion; 3-aminopropyltriethoxysilane is slowly added dropwise to the graphene oxide dispersion, and the temperature is controlled to 0-5°C and stirred continuously. After the addition is completed, the temperature is raised to 80°C, and stirring is continued for 12-24h. After the reaction is completed, it is cooled to room temperature, centrifuged at 8000rpm for 10min, washed with anhydrous ethanol repeatedly for 5 times, and vacuum dried at 50°C to constant weight to obtain modified graphene oxide; Preferably, in step B1, the ratio of the amount of graphene oxide, anhydrous ethanol and 3-aminopropyltriethoxysilane is 5 mg: 1-2 mL: 0.05-0.1 mL; Preferably, in step S3, the grafting of polyvinyl alcohol and nano-titanium dioxide is specifically prepared as follows: C1: Add polyvinyl alcohol to 20 parts by weight of deionized water, raise the temperature to 90°C, and stir until completely dissolved to obtain a transparent polyvinyl alcohol solution; add the modified graphene oxide prepared in step B1 to deionized water, stir at 200W ultrasonically for 30 minutes to disperse evenly, and obtain a modified graphene oxide solution; C2: Slowly add the modified graphene oxide solution in step C1 to the polyvinyl alcohol solution, control the temperature to 60°C, add 0.025 g / mL sodium persulfate solution, adjust the pH to 3.5 with HCl solution, continue stirring and react for 4 to 6 hours, and after the reaction is completed, cool to room temperature, centrifuge at 8000 rpm for 10 minutes, wash repeatedly with deionized water 5 times, and vacuum dry at 50°C to constant weight to obtain grafted graphene oxide; C3: TiO2 was added to anhydrous ethanol, ultrasonically treated at 200W for 30 minutes, and after uniform dispersion, KH-570 and acetic acid were added, stirred at 60°C for 2 hours, centrifuged at 8000rpm for 10 minutes, washed with anhydrous ethanol three times, and vacuum dried at 60°C to constant weight to obtain modified TiO2; C4: Add the modified TiO2 prepared in step C3 to 50 times the mass parts of deionized water, disperse it evenly by ultrasonic treatment, and obtain a modified TiO2 suspension; add the grafted graphene oxide prepared in step C2 to deionized water, disperse it evenly by ultrasonic treatment, and prepare a concentration of 5 mg / mL, then slowly add the modified TiO2 suspension, stir the reaction at room temperature for 1 to 2 hours, centrifuge at 6000 rpm for 10 minutes, wash with deionized water, and vacuum dry at 50°C to constant weight to obtain composite graphene oxide; Preferably, in step C1, the ratio of the amount of the modified graphene oxide to deionized water is 5 mg: 1 mL; in step C2, the volume ratio of the polyvinyl alcohol solution, the modified graphene oxide solution and the ammonium persulfate solution is 10-12 mL: 5-6 mL: 1 mL; in step C3, the ratio of the amount of TiO2, anhydrous ethanol, KH-570 and acetic acid is 2 g: 100 mL: 2-2.5 mL: 1-1.2 mL; in step C4, the mass ratio of modified TiO2 and grafted graphene oxide is 4: 1; Preferably, in step S4, the specific preparation steps of the in-situ polymerization reaction are as follows: D1: adding the composite graphene oxide prepared in step C4 to dimethylformamide, ultrasonically treating at 200W for 30min, dispersing uniformly, and obtaining a composite graphene oxide dispersion; dissolving polyethylene glycol diol in dimethylformamide, stirring and dissolving uniformly, and obtaining a polyethylene glycol diol solution; D2: Add dibutyltin dilaurate and trimethylolpropane to the polyethylene glycol diol solution prepared in step D1, mix well, slowly add the composite graphene oxide dispersion, disperse well by ultrasonic treatment, slowly add isocyanate, control the reaction temperature to 60-80°C, stir and react for 2-4h, cure at 60-80°C for 6-12h, and vacuum dry at 60°C to constant weight to obtain a graphene nanocomposite material; Preferably, in step D1, the ratio of the composite graphene oxide to dimethylformamide is 8-10 mg:1 mL; the ratio of the polyethylene glycol diol to dimethylformamide is 0.8-1 g:5 mL; Preferably, the ratio of the amount of dibutyltin dilaurate, trimethylolpropane, polyethylene glycol diol solution, composite graphene oxide dispersion and isocyanate in step D2 is 0.06-0.1g:0.2-0.5g:50mL:50mL:5g.
[0007] The beneficial effects of the present invention are as follows: The present invention effectively enhances the dispersibility of graphene in a polyurethane matrix through 3-aminopropyltriethoxysilane (APTES) functionalization treatment and polyvinyl alcohol (PVA) grafting, and solves the agglomeration phenomenon caused by strong van der Waals forces between graphene sheets. Specifically, APTES introduces aminosilane groups into the graphene surface through silicon-oxygen bonds. These amino groups form steric hindrances on the graphene sheet surface, destroying the π-π stacking and strong van der Waals forces between graphene sheets, and hindering the restacking and agglomeration of sheets; at the same time, the aminosilane groups can form covalent bonds with the isocyanate groups in the polyurethane matrix, significantly improving the interfacial bonding strength between graphene and polyurethane. The hydroxyl groups of PVA interact with the aminosilane groups and polyurethane segments on the graphene surface through hydrogen bonds, further enhancing the dispersibility of graphene in the polymer matrix and strengthening the interface bonding of the composite material; in addition, PVA forms a polymer coating layer on the surface of the graphene sheet, increasing the steric hindrance and hydrogen bonding, preventing the direct contact between the graphene sheets, and reducing the agglomeration caused by the van der Waals force. The flexibility and crosslinkability of the PVA segment help to improve the toughness and ductility of the composite material and avoid the increase in brittleness caused by the agglomeration of graphene. The present invention further stabilizes the dispersion state of graphene in the polyurethane matrix by introducing TiO2 nanoparticles. Although TiO2 nanoparticles mainly give the composite material excellent photocatalytic and antibacterial properties, their appropriate addition and uniform distribution synergize with the high strength of graphene to improve the impact resistance and tensile strength of the composite material.
[0008] During the synthesis of polyurethane, functionalized graphene directly participates in the polymerization reaction due to its surface active groups, ensuring that the graphene is evenly dispersed in the polyurethane matrix. Trimethylolpropane is added as a multifunctional cross-linking agent to form a highly cross-linked polyurethane network; during the in-situ polymerization process, graphene is "fixed" in the polyurethane network to prevent it from agglomerating during the curing process. The introduction of the cross-linking agent increases the cross-linking density of the polyurethane, strengthens the physical and chemical bonding between the graphene and the matrix, and improves the overall mechanical properties and thermal stability of the composite material, allowing it to maintain good performance in high temperature environments.
[0009] In summary, the present invention effectively solves the problem of graphene being easily agglomerated in a polyurethane matrix through the synergistic effect of APTES functionalization, PVA grafting, and TiO2 nanoparticles. Functionalized graphene forms covalent bonds with polyurethane chains, enhancing interfacial bonding; the introduction of PVA improves the dispersibility of graphene and the toughness of the composite material; and TiO2 nanoparticles not only give the material photocatalytic and antibacterial functions, but also further improve the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1 It is a graph showing the bending test results of the graphene nanocomposites prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3; Figure 2 Graph showing the impact test results of the graphene nanocomposites prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3; Figure 3 It is a graph showing the thermogravimetric test results of the graphene nanocomposites prepared in Example 2 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0012] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0013] Embodiment 1: A method for preparing a graphene nanocomposite material, wherein the graphene nanocomposite material comprises graphite powder, APTES, polyvinyl alcohol, nano-TiO2, polyethylene glycol, trimethylolpropane and isocyanate; The specific preparation steps of graphene nanocomposites are as follows: A1: Add 10g of graphite powder to a flask, slowly add 240mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 5°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 35°C, stir and react for 24h, after the reaction is complete, slowly add 800mL of deionized water to dilute, then add 50mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60°C to constant weight, and obtain graphene oxide; B1: Disperse 1000 mg of graphene oxide prepared in step A1 in 2000 mL of anhydrous ethanol, and perform ultrasonic treatment at 200 W for 30 min to obtain a graphene oxide dispersion; slowly drop 20 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 5°C and continue stirring. After the dropwise addition is completed, heat to 80°C and continue stirring for 12 h. After the reaction is completed, cool to room temperature, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol for 5 times, and vacuum dry at 50°C to constant weight to obtain modified graphene oxide; C1: Add 20 g of polyvinyl alcohol to 400 mL of deionized water, raise the temperature to 90°C, and stir until completely dissolved to obtain a transparent polyvinyl alcohol solution; add 1000 mg of modified graphene oxide prepared in step B1 to 200 mL of deionized water, stir at 200 W ultrasonically for 30 min to disperse evenly to obtain a modified graphene oxide solution; C2: Slowly add 200 mL of modified graphene oxide solution in step C1 into 400 mL of polyvinyl alcohol solution, control the temperature to 60°C, add 35 mL of 0.025 g / mL sodium persulfate solution, adjust the pH to 3.5 with HCl solution, continue stirring and react for 4 hours, after the reaction is completed, cool to room temperature, centrifuge at 8000 rpm for 10 minutes, wash repeatedly with deionized water 5 times, and vacuum dry at 50°C to constant weight to obtain grafted graphene oxide; C3: 10 g TiO2 was added to 500 mL anhydrous ethanol, and ultrasonic treatment was performed at 200 W for 30 min. After uniform dispersion, 11 mL KH-570 and 5.5 mL acetic acid were added, and the mixture was stirred at 60 °C for 2 h. The mixture was centrifuged at 8000 rpm for 10 min, and washed with anhydrous ethanol for 3 times. The mixture was vacuum dried at 60 °C to constant weight to obtain modified TiO2. C4: Add 4g of modified TiO2 prepared in step C3 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and obtain a modified TiO2 suspension; add 1000mg of grafted graphene oxide prepared in step C2 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and prepare a concentration of 5mg / mL, then slowly add the modified TiO2 suspension, stir the reaction at room temperature for 1h, centrifuge at 6000rpm for 10min, wash with deionized water, and vacuum dry at 50°C to constant weight to obtain composite graphene oxide; D1: 1000 mg of the composite graphene oxide prepared in step C4 was added to 125 mL of dimethylformamide, and ultrasonically treated at 200 W for 30 min to disperse uniformly to obtain a composite graphene oxide dispersion; 32 g of polyethylene glycol diol was dissolved in 200 mL of dimethylformamide, and stirred to dissolve uniformly to obtain a polyethylene glycol diol solution; D2: Add 0.24 g of dibutyltin dilaurate and 0.8 g of trimethylolpropane to 200 mL of polyethylene glycol diol solution prepared in step D1, mix well, slowly add 200 mL of composite graphene oxide dispersion, disperse evenly by ultrasonic treatment, slowly add 20 g of isocyanate, control the reaction temperature to 60°C, stir the reaction for 2 h, cure at 60°C for 12 h, and vacuum dry at 60°C to constant weight to obtain a graphene nanocomposite material.
[0014] Embodiment 2: A method for preparing a graphene nanocomposite material, wherein the graphene nanocomposite material comprises graphite powder, APTES, polyvinyl alcohol, nano-TiO2, polyethylene glycol, trimethylolpropane and isocyanate; The specific preparation steps of graphene nanocomposites are as follows: A1: Add 10g of graphite powder to a flask, slowly add 240mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 0℃, stir and mix to disperse evenly, control the temperature to 10℃, slowly add 30g of potassium permanganate, after the addition is complete, raise the temperature to 40℃, stir and react for 24h, after the reaction is complete, slowly add 1000mL of deionized water to dilute, then add 600mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60℃ to constant weight, and obtain graphene oxide; B1: Disperse 1000 mg of graphene oxide prepared in step A1 in 1000 mL of anhydrous ethanol, and perform ultrasonic treatment at 200 W for 60 min to obtain a graphene oxide dispersion; slowly drop 10 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 0°C and continue stirring, after the dropwise addition is completed, heat to 80°C, continue stirring for 24 h, cool to room temperature after the reaction is completed, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol for 5 times, and vacuum dry at 50°C to constant weight to obtain modified graphene oxide; C1: Add 20 g of polyvinyl alcohol to 400 mL of deionized water, raise the temperature to 90°C, and stir until completely dissolved to obtain a transparent polyvinyl alcohol solution; add 1000 mg of modified graphene oxide prepared in step B1 to 200 mL of deionized water, stir at 200 W ultrasonically for 30 min to disperse evenly to obtain a modified graphene oxide solution; C2: Slowly add 200 mL of modified graphene oxide solution in step C1 into 400 mL of polyvinyl alcohol solution, control the temperature to 60°C, add 40 mL of 0.025 g / mL sodium persulfate solution, adjust the pH to 3.5 with HCl solution, continue stirring and react for 6 hours, after the reaction is completed, cool to room temperature, centrifuge at 8000 rpm for 10 minutes, wash repeatedly with deionized water 5 times, and vacuum dry at 50°C to constant weight to obtain grafted graphene oxide; C3: 10 g TiO2 was added to 500 mL anhydrous ethanol, and ultrasonic treatment was performed at 200 W for 30 min. After uniform dispersion, 10 mL KH-570 and 5 mL acetic acid were added, and the mixture was stirred at 60 °C for 2 h. The mixture was centrifuged at 8000 rpm for 10 min, and washed with anhydrous ethanol for 3 times. The mixture was vacuum dried at 60 °C to constant weight to obtain modified TiO2. C4: Add 4g of modified TiO2 prepared in step C3 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and obtain a modified TiO2 suspension; add 1000mg of grafted graphene oxide prepared in step C2 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and prepare a concentration of 5mg / mL, then slowly add the modified TiO2 suspension, stir the reaction at room temperature for 2h, centrifuge at 6000rpm for 10min, wash with deionized water, and vacuum dry at 50°C to constant weight to obtain composite graphene oxide; D1: 1000 mg of the composite graphene oxide prepared in step C4 was added to 100 mL of dimethylformamide, and ultrasonically treated at 200 W for 30 min to disperse uniformly to obtain a composite graphene oxide dispersion; 40 g of polyethylene glycol diol was dissolved in 200 mL of dimethylformamide, and stirred to dissolve uniformly to obtain a polyethylene glycol diol solution; D2: Add 0.4 g of dibutyltin dilaurate and 2 g of trimethylolpropane to 200 mL of polyethylene glycol diol solution prepared in step D1, mix well, slowly add 200 mL of composite graphene oxide dispersion, disperse evenly by ultrasonic treatment, slowly add 20 g of isocyanate, control the reaction temperature to 80°C, stir the reaction for 4 hours, cure at 80°C for 12 hours, and vacuum dry at 60°C to constant weight to obtain a graphene nanocomposite material.
[0015] Embodiment 3: A method for preparing a graphene nanocomposite material, wherein the graphene nanocomposite material comprises graphite powder, APTES, polyvinyl alcohol, nano-TiO2, polyethylene glycol, trimethylolpropane and isocyanate; The specific preparation steps of graphene nanocomposites are as follows: A1: Add 10g of graphite powder to a flask, slowly add 240mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the reaction temperature to 4°C, stir and mix to disperse evenly, control the temperature to 10°C, slowly add 30g of potassium permanganate, raise the temperature to 38°C after the addition is complete, stir and react for 18h, after the reaction is complete, slowly add 900mL of deionized water to dilute, then add 550mL of hydrogen peroxide to terminate the reaction, centrifuge at 8000rpm for 10min, repeat washing with deionized water and 1M HCl solution 3 times, dry at 60°C to constant weight, and obtain graphene oxide; B1: Disperse 1000 mg of graphene oxide prepared in step A1 in 1600 mL of anhydrous ethanol, and perform ultrasonic treatment at 200 W for 50 min to obtain a graphene oxide dispersion; slowly drop 16 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature to 4°C and continue stirring, after the dropwise addition is completed, heat to 80°C, continue stirring for 18 h, cool to room temperature after the reaction is completed, centrifuge at 8000 rpm for 10 min, wash repeatedly with anhydrous ethanol for 5 times, and vacuum dry at 50°C to constant weight to obtain modified graphene oxide; C1: Add 20 g of polyvinyl alcohol to 400 mL of deionized water, raise the temperature to 90°C, and stir until completely dissolved to obtain a transparent polyvinyl alcohol solution; add 1000 mg of modified graphene oxide prepared in step B1 to 200 mL of deionized water, stir at 200 W ultrasonically for 30 min to disperse evenly to obtain a modified graphene oxide solution; C2: Slowly add 200 mL of modified graphene oxide solution in step C1 to 396 mL of polyvinyl alcohol solution, control the temperature to 60°C, add 33 mL of 0.025 g / mL sodium persulfate solution, adjust the pH to 3.5 with HCl solution, continue stirring and react for 5 hours, after the reaction is completed, cool to room temperature, centrifuge at 8000 rpm for 10 minutes, wash repeatedly with deionized water 5 times, and vacuum dry at 50°C to constant weight to obtain grafted graphene oxide; C3: 10 g TiO2 was added to 500 mL anhydrous ethanol, and ultrasonic treatment was performed at 200 W for 30 min. After uniform dispersion, 12.5 mL KH-570 and 6 mL acetic acid were added, and the mixture was stirred at 60 °C for 2 h. The mixture was centrifuged at 8000 rpm for 10 min, and washed with anhydrous ethanol for 3 times. The mixture was vacuum dried at 60 °C to constant weight to obtain modified TiO2. C4: Add 4g of modified TiO2 prepared in step C3 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and obtain a modified TiO2 suspension; add 1000mg of grafted graphene oxide prepared in step C2 to 200mL of deionized water, disperse it evenly by ultrasonic treatment, and prepare a concentration of 5mg / mL, then slowly add the modified TiO2 suspension, stir the reaction at room temperature for 1.5h, centrifuge at 6000rpm for 10min, wash with deionized water, and vacuum dry at 50°C to constant weight to obtain composite graphene oxide; D1: 1000 mg of the composite graphene oxide prepared in step C4 was added to 110 mL of dimethylformamide, and ultrasonically treated at 200 W for 30 min to disperse uniformly to obtain a composite graphene oxide dispersion; 35 g of polyethylene glycol diol was dissolved in 200 mL of dimethylformamide, and stirred to dissolve uniformly to obtain a polyethylene glycol diol solution; D2: Add 0.35 g of dibutyltin dilaurate and 1.5 g of trimethylolpropane to 200 mL of polyethylene glycol diol solution prepared in step D1, mix well, slowly add 200 mL of composite graphene oxide dispersion, disperse evenly by ultrasonic treatment, slowly add 20 g of isocyanate, control the reaction temperature to 70°C, stir the reaction for 3 h, cure at 70°C for 10 h, and vacuum dry at 60°C to constant weight to obtain a graphene nanocomposite material.
[0016] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that, in Comparative Example 1, the graphene oxide is not subjected to APTES functionalization treatment, and the untreated graphene oxide is directly mixed with polyethylene glycol for reaction.
[0017] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that Comparative Example 2 uses APTES-functionalized graphene oxide, but does not perform PVA grafting treatment, and directly performs in-situ polymerization with polyethylene glycol diol.
[0018] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that in Comparative Example 3, no TiO2 nanoparticles are added to the composite material.
[0019] Performance Testing: Tensile test: The nanographene composite material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were fixed in the fixture of a universal material testing machine, a tensile speed of 10 mm / min was used, the initial tensile force was set to 0 N, and the sample was ensured to start the test without initial stress. The testing machine was started and the tensile load was continuously applied until the sample broke, and the tensile strength and elongation at break were recorded and calculated. The results are shown in Table 1 below; Table 1. Tensile strength test results
[0020] It can be seen from the results in Table 1 that the nano-graphene composite material prepared by the present invention has good mechanical properties and certain toughness, and is suitable for high-strength applications; it can be seen from the results of Example 2 and Comparative Example 1 that unfunctionalized graphene oxide may cause poor dispersion of graphene in the polyurethane matrix, easy agglomeration, resulting in weak interface bonding force, lack of interface enhancement mechanism, which will reduce the overall mechanical properties of the material, and thus lead to low tensile strength. At the same time, due to the agglomeration of graphene, the ductility of the composite material is poor, which leads to a decrease in elongation at break; it can be seen from the results of Example 2 and Comparative Example 2 that polyvinyl alcohol strengthens the interface bonding through hydrogen bonds to form a coating layer, thereby increasing the dispersion and toughness of graphene; lack of polyvinyl alcohol grafting, the dispersion of graphene is affected, and partial agglomeration may still exist, resulting in the toughness and ductility of the material being affected; it can be seen from the results of Example 3 and Comparative Example 2 that the introduction of TiO2 plays a role in enhancing the dispersion stability and mechanical properties of graphene, and the lack of such synergistic effect causes the elongation at break and tensile strength of the material to be affected to a certain extent.
[0021] Bending test: The nanographene composite samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were placed horizontally on the support frame of a three-point bending tester, with the support point spacing being 80% of the sample length, the bending speed being set to 1 mm / min, the initial load being set to 0 N, and the bending strength being recorded. The results are shown in FIG. Figure 1 shown.
[0022] Depend on Figure 1 As can be seen from the results, the graphene nanocomposite material prepared by the present invention has excellent flexural strength; from the results of Example 2 and Comparative Example 1, it can be seen that due to the lack of APTES functionalization, the interface bonding between graphene and polyurethane is weak, and the agglomeration of graphene in the matrix is more serious, which will lead to poor stress transfer ability of the composite material, and the material is easy to break when bent, which in turn leads to a significant impact on the flexural strength; from the results of Comparative Example 2 and Example 2, it can be seen that due to the lack of polyvinyl alcohol grafting, the flexibility and ductility of the composite material are limited, and although the dispersion and interface bonding strength of the graphene sheets are improved, there is no flexible segment and steric hindrance of polyvinyl alcohol, which leads to a significant impact on its flexural strength; from the results of Comparative Example 3 and the embodiment, it can be seen that TiO2 improves the mechanical properties of the material through the synergistic effect with graphene, and its absence causes the flexural strength to be affected to a certain extent.
[0023] Impact test: The nanographene composite material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were vertically mounted on the sample fixture of the impact tester, ensuring that the notch was located directly opposite the impact position. The tester was started, and the pendulum was released to hit the sample. The energy difference before and after the pendulum impact was recorded, and the energy absorption capacity of the material was calculated. The impact strength was calculated based on the absorbed energy and the cross-sectional area of the sample. The results are shown in FIG. Figure 2 shown.
[0024] Depend on Figure 2 The results show that the graphene nanocomposite material prepared by the present invention has excellent impact resistance; from the results of comparative example 1 and example 2, it can be seen that without APTES functionalization treatment, the graphene agglomerates, resulting in lower impact strength of the material; from the results of comparative example 2 and example 2, it can be seen that the lack of synergistic reinforcement effect of polyvinyl alcohol grafting leads to relatively poor toughness and dispersibility of the material, and the impact strength is affected; from the results of comparative example 3 and example 2, it can be seen that the lack of TiO2 slightly affects the impact strength of the material.
[0025] Thermogravimetric analysis test: The graphene nanocomposites prepared in Example 2 and Comparative Examples 1 to 3 were placed in a TGA device, and the temperature was raised to 200°C, 300°C and 500°C at a rate of 10°C / min under a nitrogen atmosphere. The mass loss percentage was tested at 200°C, 300°C and 500°C, and the results were recorded as follows: Figure 3 shown.
[0026] Depend on Figure 3 As can be seen from the results, the graphene nanocomposite material prepared by the present invention has excellent thermal stability and can have a higher residual amount at high temperature; from the results of Comparative Example 1 and Example 2, it can be seen that the interface bonding between graphene without APTES functionalization and polyurethane is weak, which may lead to agglomeration of graphene sheets and poor dispersion of graphene, affecting thermal stability; from the results of Comparative Example 2 and Example 2, it can be seen that without polyvinyl alcohol grafting, the functionalized graphene is strongly bonded to polyurethane, but the lack of the coating effect of polyvinyl alcohol reduces the dispersion of graphene and the toughness of the composite material, and the thermal decomposition is affected; from the results of Comparative Example 3 and Example 2, it can be seen that polyvinyl alcohol grafting improves the dispersion of the composite material, but the lack of TiO2 affects the performance at high temperature.
[0027] Chemical corrosion resistance test: The graphene nanocomposites prepared in Example 2 and Comparative Examples 1 to 3 were tested in a 5% NaCl solution at a temperature of 35±2° C. for 168 h, and the mass loss and appearance change were recorded. The results are shown in Table 2 below.
[0028] Table 2. Chemical corrosion resistance test results of graphene nanocomposites
[0029] It can be seen from the results in Table 2 that the graphene nanocomposite prepared by the present invention has excellent chemical corrosion resistance; it can be seen from the results of Comparative Example 1 and Example 2 that due to the poor dispersibility of graphene in the matrix and weak interface bonding, moisture and salt can more easily penetrate into the composite material, causing the polyurethane matrix to decompose due to corrosion, thereby causing more significant mass loss and appearance changes; it can be seen from the results of Comparative Example 2 and Example 2 that the functionalized graphene oxide is covalently bonded to the polyurethane matrix, but lacks the protection and steric hindrance of the polyvinyl alcohol grafted layer on the graphene sheets, and some agglomeration may still exist between the graphene sheets, resulting in an increase in the mass loss of the graphene nanocomposite; it can be seen from the results of Comparative Example 3 and Example 2 that the overall corrosion resistance of the composite material is significantly affected by the lack of the stabilizing effect of TiO2 nanoparticles.
[0030] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a graphene nanocomposite material, characterized in that: The graphene nanocomposite material comprises graphite powder, APTES, polyvinyl alcohol, nano-TiO2, polyethylene glycol, trimethylolpropane and isocyanate; The specific preparation steps of the graphene nanocomposite material are as follows: S1: Preparation of graphene oxide; Preparation of graphene oxide using a modified Hummers method; S2: introduction of aminosilane groups into graphene oxide; S3: Grafting polyvinyl alcohol and nano-titanium dioxide; through the action of initiator ammonium persulfate, polyvinyl alcohol is grafted onto the graphene oxide introduced with aminosilane groups in step S2, and then the surface-modified nano-TiO2 is introduced; S4: In-situ polymerization and grafting of modified graphene oxide and polyurethane polyol to obtain graphene nanocomposites; The graphene nanocomposite material is prepared by selecting hydrophilic polyol polyethylene glycol diol, adding dibutyltin dilaurate catalyst and trimethylolpropane crosslinking agent.
2. The method for preparing a graphene nanocomposite material according to claim 1, characterized in that: In step S1, the specific preparation steps of the graphene oxide are as follows: A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the reaction temperature, stir and mix to disperse evenly, control the temperature, slowly add potassium permanganate, increase the temperature after the addition is complete, stir and react, after the reaction is complete, slowly add deionized water to dilute, then add hydrogen peroxide to terminate the reaction, centrifuge, repeat washing with deionized water and HCl solution for 3 times, dry to constant weight, and obtain graphene oxide.
3. The method for preparing a graphene nanocomposite material according to claim 2, characterized in that: In step A1, the ratio of the amount of the graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:24mL:3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:5-6mL:1g.
4. The method for preparing a graphene nanocomposite material according to claim 3, characterized in that: In step S2, the introduction of the aminosilane group is specifically prepared as follows: B1: Disperse the graphene oxide prepared in step A1 in anhydrous ethanol and perform ultrasonic treatment to obtain a graphene oxide dispersion; slowly drop 3-aminopropyltriethoxysilane into the graphene oxide dispersion, control the temperature and continue stirring. After the dropwise addition is completed, increase the temperature and continue stirring. After the reaction is completed, cool to room temperature, centrifuge, wash with anhydrous ethanol, and vacuum dry to constant weight to obtain modified graphene oxide.
5. The method for preparing a graphene nanocomposite material according to claim 4, characterized in that: In step B1, the ratio of the amount of graphene oxide, anhydrous ethanol and 3-aminopropyltriethoxysilane is 5 mg: 1-2 mL: 0.05-0.1 mL.
6. The method for preparing a graphene nanocomposite material according to claim 5, characterized in that: In step S3, the grafting of polyvinyl alcohol and nano-titanium dioxide is specifically prepared as follows: C1: adding polyvinyl alcohol to deionized water, raising the temperature, stirring until completely dissolved, and obtaining a transparent polyvinyl alcohol solution; adding the modified graphene oxide prepared in step B1 to deionized water, stirring by ultrasonication, and dispersing uniformly to obtain a modified graphene oxide solution; C2: slowly adding the modified graphene oxide solution in step C1 to the polyvinyl alcohol solution, controlling the temperature, adding sodium persulfate solution, adjusting the pH with HCl solution, and continuously stirring the reaction. After the reaction is completed, cooling to room temperature, centrifuging, washing with deionized water, and vacuum drying to constant weight to obtain grafted graphene oxide; C3: Add TiO2 to anhydrous ethanol, perform ultrasonic treatment, and after uniform dispersion, add KH-570 and acetic acid, stir to react, centrifuge, wash with anhydrous ethanol, and vacuum dry to constant weight to obtain modified TiO2; C4: adding the modified TiO2 prepared in step C3 to deionized water, dispersing it evenly by ultrasonic treatment, and obtaining a modified TiO2 suspension; adding the grafted graphene oxide prepared in step C2 to deionized water, dispersing it evenly by ultrasonic treatment, and then slowly adding the modified TiO2 suspension, stirring the reaction at room temperature, centrifuging, washing with deionized water, and vacuum drying to constant weight to obtain composite graphene oxide.
7. The method for preparing a graphene nanocomposite material according to claim 6, characterized in that: In step C1, the ratio of the amount of the modified graphene oxide to deionized water is 5 mg:1 mL; in step C2, the volume ratio of the polyvinyl alcohol solution, the modified graphene oxide solution and the ammonium persulfate solution is 10-12 mL:5-6 mL:1 mL; in step C3, the ratio of the amount of TiO2, anhydrous ethanol, KH-570 and acetic acid is 2 g:100 mL:2-2.5 mL:1-1.2 mL; in step C4, the mass ratio of modified TiO2 and grafted graphene oxide is 4:
1.
8. The method for preparing a graphene nanocomposite material according to claim 7, characterized in that: In step S4, the specific preparation steps of the in-situ polymerization reaction are as follows: D1: adding the composite graphene oxide prepared in step C4 to dimethylformamide, performing ultrasonic treatment, and dispersing the composite graphene oxide uniformly to obtain a composite graphene oxide dispersion; dissolving polyethylene glycol diol in dimethylformamide, stirring and dissolving the polyethylene glycol diol uniformly to obtain a polyethylene glycol diol solution; D2: Add dibutyltin dilaurate and trimethylolpropane to the polyethylene glycol diol solution prepared in step D1, mix well, slowly add the composite graphene oxide dispersion, disperse evenly by ultrasonic treatment, slowly add isocyanate, control the reaction temperature, stir the reaction, solidify, and vacuum dry to constant weight to obtain a graphene nanocomposite material.
9. The method for preparing a graphene nanocomposite material according to claim 8, characterized in that: In step D1, the ratio of the composite graphene oxide to dimethylformamide is 8-10 mg:1 mL; the ratio of the polyethylene glycol diol to dimethylformamide is 0.8-1 g:5 mL; and the ratio of the dibutyltin dilaurate, trimethylolpropane, polyethylene glycol diol solution, composite graphene oxide dispersion and isocyanate in step D2 is 0.06-0.1 g:0.2-0.5 g:50 mL:50 mL:5 g.
Citation Information
Patent Citations
Preparation method of graphene oxide / waterborne polyurethane nanometer composite material
CN103254400A
Graphene-polyvinyl alcohol hybrid material and method of preparing polyurethane resin-based composite material
CN106065148A
Graphene nanoparticle composite material and preparation method thereof
CN107400396A
Preparation method of graphene-carbon nanotube / waterborne polyurethane composite material
CN108264755A
Graphene modified polymer material and preparation method thereof
CN112029228A
Cited By
Graphene modified TPU (thermoplastic polyurethane) heat-conducting tire lining layer and preparation method thereof
CN120623761A